(untitled) (Revista Paradigma, 2022)
The objective of this article is to bring the postulates of ethics of care, in its gender aspect, to the contributions of ecofeminism and feminist ecological economics, as a form of female emancipation and a proposal for action aimed at sustainable development, under the terms of the Objectives Sustainable Development established by the United Nations. It is stated that the contributions of women, with regard to the implementation of environmental management aimed at sustainability, can favor harmonious coexistence between humans and non-humans. Applying the principles of ecofeminism and feminist ecological economics to the ethics of care, it is possible, through the creation of public policies, to give effectiveness to the active participation of women in decision-making on environmental issues. Therefore, initially, ecofeminism is approached as a movement to fight the socioeconomic impacts caused by incessant profit and the depletion of natural resources. Next, the environmental impacts felt by the most vulnerable strata of society are analyzed, which led, among other reasons, to the formation of a new idea of ​​environmental management by feminism, called feminist ecological economics. Since then, it is highlighted that this feminist materialist model, essential for the understanding of feminist ecosystemism represents, together with the ethics of care, one of the alternative paths to social transformation with the consequent female emancipation, which at the same time, aims to achieve longed for environmental sustainability. The scientific deductive method is used in which general considerations are formulated to conclude with the specific one, together with bibliographic research techniques.